2023
DOI: 10.1186/s12889-023-15245-2
|View full text |Cite
|
Sign up to set email alerts
|

The home language environment in rural China: variations across family characteristics

Abstract: Background A rich language environment is an important element of a nurturing home environment. Despite their proven importance, vocabulary and conversation have been shown to vary widely across households—even within the same socio-economic class. One significant gap in the existing literature is its nearly exclusive geographic focus on Western and developed settings, with little attention given to poorer communities in lower/middle income countries. The purpose of this study was to empiricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…We acknowledge several limitations of this study. First, while LENA has been validated and confirmed reliable in Mandarin Chinese (Gilkerson et al., 2015; Ma et al., 2023) and used previously among children aged 0 through 3 years in China (Ma et al., 2021; Zhang, Xu, et al., 2015), other studies suggest that the accuracy of CTC (especially in the measures of initiated segments, etc.) is not fully reliable (Cristia et al., 2020, 2021).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…We acknowledge several limitations of this study. First, while LENA has been validated and confirmed reliable in Mandarin Chinese (Gilkerson et al., 2015; Ma et al., 2023) and used previously among children aged 0 through 3 years in China (Ma et al., 2021; Zhang, Xu, et al., 2015), other studies suggest that the accuracy of CTC (especially in the measures of initiated segments, etc.) is not fully reliable (Cristia et al., 2020, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…LENA‐reported AWC, CTC, and CVC have all been reliably used in previous studies in the United States, China, and other countries (Busch et al., 2018; Canault et al., 2016; Gilkerson et al., 2018; Pae et al., 2016; Weisleder & Fernald, 2013; Zhang, Xu, et al., 2015). All three measures have been found to correlate closely with word counts generated from human manual transcription, including among Chinese‐speaking populations (Standard Mandarin and Shanghai dialect; Gilkerson et al., 2015; Ma et al., 2023).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…There is also evidence of rural-urban disparities in the home language environment: a series of studies describing and comparing the home language environments of young children in low-SES households in rural Shaanxi Province to that of high-SES households in urban Shanghai demonstrated that rural children overheard significantly less adult speech and have fewer adult-child verbal interactions compared to their urban peers [ 35 37 ], demonstrated that rural children overhear significantly less speech and have fewer adult-child verbal interactions compared to their urban peers. Another study among low SES rural households in two southwestern counties of China similarly found lower counts of adult words and adult-child conversation [ 38 ].…”
Section: Introductionmentioning
confidence: 99%